Effect of electrolytes as adjuvants in GFP and LPS partitioning on aqueous two-phase systems: 2. Nonionic micellar systems - Teixeira-Pinto, Renata Garcia Rodrigues; Molino, João Vitor Dutra; Santos-Ebinuma, Valéria Carvalho [UNESP]; Pessoa, Adalberto; Valentini, Sandro Roberto; Pereira, Jorge Fernando Brandão [UNESP]; Lopes, André Moreni [UNESP] (Elsevier, 2019)
Lipopolysaccharide endotoxins (LPS) are the most common contaminant pyrogenic compounds found in intracellular recombinant biomolecules purified from Gram-negative bacteria, such as Escherichia coli. Thus, the purification downstream processing should guarantee the effective removal of LPS from the final bioproduct, particularly, therapeutic biopharmaceuticals. Aqueous two-phase micellar systems (ATPMS) appear to be an excellent strategy to purify recombinant biopharmaceuticals from the cell lysate of E. coli, reducing high LPS concentrations. In order to demonstrate the effectiveness of ATPMS as a biopharmaceutical purification platform, the influence of inorganic salt electrolytes (NaCl, Li2SO4, KI, or KNO3) on the partitioning of green fluorescent protein (GFP) and LPS removal using ATPMS composed of n-decyl tetraethylene oxide (C10E4) was evaluated. The impact of different LPS concentrations on GFP partitioning was also studied. The addition of electrolytes (i.e., NaCl or Li2SO4) to the C10E4-based ATPMS have reduced the phase forming temperatures to very mild conditions (ca. 17.00 and 13.00 °C, for NaCl and Li2SO4, respectively). The selective partitioning ability of the proposed ATPMS was further demonstrated, where a complete removal of the LPS from the micelle-poor phase (REMLPS > 98%) and a preferential GFP recovery (RECGFP = 97%, KGFP > 7) to the micelle-poor phase was obtained. The GFP partitioning was even enhanced by increasing LPS loading (104–106 EU/mL), probably due to the formation of mixed micelles between LPS and C10E4. It is here demonstrated that a C10E4/buffer + salt-based ATPMS can be a useful and straightforward platform for the removal of endotoxin contaminants and the purification of recombinant biopharmaceuticals from E. coli cell lysates.
Keywords: Aqueous two-phase micellar systems (ATPMS); Biopharmaceutical purification; C10E4; Green fluorescent protein (GFP); Inorganic salts; Lipopolysaccharide (LPS) removal